Influence of calcium hydroxide dressing and two irrigants on the filling of artificial lateral canals - Marili Doro Andrade Deonizio; Betânia Drummond Duarte Teixeira; Marilisa Carneiro Leão Gabardo; Antonio Batista; Alexandre Kowalczuck; Gilson Blitzkow Sydney (Indian Journal of Dental Research, 2015)
Context: This study was carried out on the assumption that calcium hydroxide [Ca(OH) 2 ] dressing and irrigants may influence the obturation of lateral canals. Aims: To evaluate the influence of 2.5% sodium hypochlorite (NaOCl), 2% chlorhexidine (CHX) gel and Ca(OH) 2 on the filling of artificial lateral canals. Settings and Design: Ex vivo quantitative laboratory study. Materials and Methods: Forty-two human mandibular premolars were selected. After cavity access, six lateral canals were performed, two in each root section, one mesial and one on the distal root surface. After preparation, the specimens were randomly divided into four groups: Group I: Under irrigation with 2% CHX and saline solution and with intracanal dressing Ca(OH) 2 paste; Group II: The same preparation as Group I, but without Ca(OH) 2 ; Group III: Under irrigation with 2.5% NaOCl without Ca(OH) 2 ; and Group IV: The same preparation as Group III, but with Ca(OH) 2 . Two teeth without intracanal dressing were used as negative controls. Lateral condensation technique was performed. Then, digital radiographic images were obtained. Statistical Analysis Used: Data were analyzed using SPSS 17.0, submitted to Kappa (reliability between examiners) and Kruskal-Wallis test. Results: No statistical difference was registered between Groups II and III in all root sections (P > 0.05), but it was observed between Groups I and IV (P < 0.05), except on the apical section (P > 0.05). In all sections, the Group I filled more artificial lateral canals than in Group IV. Conclusions: The irrigants tested had no influence on the filling of artificial lateral canals. Nevertheless, intracanal dressing of Ca(OH) 2 influenced this filling.